A Perceptual Analysis of Standard Safety, Fluorescent, and Neon Colors. (September 2014) - Zielinska, Olga A.; Wogalter, Michael S.; Mayhorn, Christopher B.
Twenty-six standard safety colors specified by the American National Standards Institute (ANSI), International Standards Organization (ISO), and the Federal Highway Association (FHWA) were compared to seven fluorescent and neon colors on perceived hazard and perceived importance. Results indicated that the fluorescent orange, ANSI red, fluorescent yellow, FHWA red, fluorescent yellow green, and ISO red were the highest rated colors on perceived hazard. ANSI red, FHWA red, ISO red, fluorescent orange, fluorescent yellow, and fluorescent yellow green were rated the highest on perceived importance. The implications of these findings and the potential use of fluorescent colors in product warnings are discussed.